2020
DOI: 10.1186/s12864-020-6512-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic response to three osmotic stresses in gills of hybrid tilapia (Oreochromis mossambicus female × O. urolepis hornorum male)

Abstract: Background: Osmotic stress is a widespread phenomenon in aquatic animal. The ability to cope with salinity stress and alkaline stress is quite important for the survival of aquatic species under natural conditions. Tilapia is an important commercial euryhaline fish species. What's more tilapia is a good experimental material for osmotic stress regulation research, but the molecular regulation mechanism underlying different osmotic pressure of tilapia is still unexplored. Results: To elucidate the osmoregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 76 publications
2
36
0
Order By: Relevance
“…In agreement with our finding, the functional involvements of slc4a4 in the gills were reported in eel (Anguilla rostrata) [43]. In addition, as the intestinal HCO 3 − secretion is the key mechanism to enable luminal aggregate formation and water absorption, and transepithelial movement of basolateral HCO 3 − is mediated by slc4a4 present in the basolateral membrane, several studies have reported the essential function of Slc4a4 in the intestine of marine fishes like European sea bass (Dicentrarchus labrax), sea bream (Sparus aurata L.), Mozambique tilapia (Oreochromis mossambicus) [13,44,45], and hybrid tilapia (Oreochromis mossambicus female × O. urolepis hornorum male) [46]. In that case, the expression pattern of slc4a4 needs to be investigated in spotted sea bass in a future study.…”
Section: Na + -Coupled Bicarbonate Transporters (Ncbts)mentioning
confidence: 99%
“…In agreement with our finding, the functional involvements of slc4a4 in the gills were reported in eel (Anguilla rostrata) [43]. In addition, as the intestinal HCO 3 − secretion is the key mechanism to enable luminal aggregate formation and water absorption, and transepithelial movement of basolateral HCO 3 − is mediated by slc4a4 present in the basolateral membrane, several studies have reported the essential function of Slc4a4 in the intestine of marine fishes like European sea bass (Dicentrarchus labrax), sea bream (Sparus aurata L.), Mozambique tilapia (Oreochromis mossambicus) [13,44,45], and hybrid tilapia (Oreochromis mossambicus female × O. urolepis hornorum male) [46]. In that case, the expression pattern of slc4a4 needs to be investigated in spotted sea bass in a future study.…”
Section: Na + -Coupled Bicarbonate Transporters (Ncbts)mentioning
confidence: 99%
“…The CSR machinery responds to sodium-destabilized proteins by overexpressing molecular chaperones, such as heat shock proteins (T. G. Evans & Kultz, 2020), two of which were temporarily upregulated in Arabian pupfish at 24 hours, as well as in a hyperosmotic challenged Sacramento splittail population (Mundy et al, 2020). Rising intracellular sodium levels can also cause nucleic acid structural disruptions (T. G. Evans & Kultz, 2020), and consequently, increased expressions of DNA damage related genes are often reported as part of the CSR following hyperosmotic stress in teleosts (Brennan et al, 2015;Su, Ma, Zhu, Liu, & Gao, 2020;Whitehead et al, 2013). In Arabian pupfish several DNA damage related genes were transiently upregulated especially in the first 24 hours of exposure, like serum/glucocorticoid regulated kinase 1 (SGK1), and similarly increased in other fish following acute seawater challenges (T. G. Evans & Somero, 2008;Shaw et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In a broader sense, transcriptome analyses in teleost fishes continue to facilitate the identification of novel genes involved in osmoregulation. [58][59][60][61][62][63] In the mammalian kidney, a functional hyperosmotic cis-response element was identified in cells of the renal medulla exposed to dramatic changes in extracellular osmolality. 64 This osmotic-response element (ORE), also called tonicity-responsive enhancer, regulates genes involved in the accumulation of compatible osmolytes (i.e.…”
Section: In S Ili Co and In Vitro Identific Ation Of Tr Anscrip Tiomentioning
confidence: 99%
“…hypo‐ vs hyperosmotic extracellular conditions). In a broader sense, transcriptome analyses in teleost fishes continue to facilitate the identification of novel genes involved in osmoregulation 58‐63 …”
Section: In Silico and In Vitro Identification Of Transcriptional Regmentioning
confidence: 99%